KEBIJAKAN PROFESIONALISME GURU DI MINU MIFTAHUL FALAH TEGAL KIDUL, PASURUAN - Liswanto; Barnoto; Ashari (LPPM IAI Almuslim Aceh, 2025)
The results of the research that has been done show that with the Minu Miftahul Falah teacher certification policy in Tegal Kidul, Pasuruan, teachers respond positively to this policy. There are six teachers who have obtained certification from 2011 to 2023. The motivation is to improve work ability in order to improve the quality of education in the MI where the teacher serves. Teachers Minu Miftahul Falah Tegal Kidul, Pasuruan generally have a good understanding of teacher professionalism, the characteristics of professional teachers, and have good efforts to improve teacher professionalism. The level of professionalism of certified teachers is high. The certification policy for Minu Miftahul Falah teachers in Tegal Kidul, Pasuruan has had a positive impact on increasing teacher professionalism. This is shown by the teacher's ability to carry out tasks accompanied by high discipline and responsibility and continue to strive to improve the quality of education in madrasas.